Analysis of a minority language's standardisation through the situation of Kven and Meänkieli - Boudier, Hadrien (HAL CCSD, 2023)
International audience Explanation of my PhD research planning, progress and intention related to Kven and Meänkieli for the occasion of the Kvensk forsknings- og utdanningsseminar